2001
DOI: 10.1182/blood.v97.7.2151
|View full text |Cite
|
Sign up to set email alerts
|

Reduced oxidative-stress response in red blood cells from p45NFE2-deficient mice

Abstract: p45NF-E2 is a member of the cap 'n' collar (CNC)-basic leucine zipper family of transcriptional activators that is expressed at high levels in various types of blood cells. Mice deficient in p45NF-E2 that were generated by gene targeting have high mortality from bleeding resulting from severe thrombocytopenia. Surviving p45nf-e2 ؊/؊ adults have mild anemia characterized by hypochromic red blood cells (RBCs), reticulocytosis, and splenomegaly. Erythroid abnormalities in p45nf-e2 ؊/؊ animals were previously attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Because certain of these genes are probably regulated through an ARE, these observations are consistent with a role for Nrf1 in regulating ARE-dependent gene expression. Furthermore, loss of NF-E2 p45 is associated with abrogated expression of mGSTA3 in murine red blood cells (Chan et al, 2001). Figure 11 shows that although loss of Nrf2 is consistently associated with a reduction in mGSTA3 expression levels, the magnitude of this reduction varies between mouse tissues.…”
Section: Downloaded Frommentioning
confidence: 92%
See 1 more Smart Citation
“…Because certain of these genes are probably regulated through an ARE, these observations are consistent with a role for Nrf1 in regulating ARE-dependent gene expression. Furthermore, loss of NF-E2 p45 is associated with abrogated expression of mGSTA3 in murine red blood cells (Chan et al, 2001). Figure 11 shows that although loss of Nrf2 is consistently associated with a reduction in mGSTA3 expression levels, the magnitude of this reduction varies between mouse tissues.…”
Section: Downloaded Frommentioning
confidence: 92%
“…Of particular relevance to the selective toxicity of AFB 1 is the observation that expression of mGSTA3 is reduced in mouse lines with targeted disruption of CNC bZIP genes. Specifically, red blood cells from NF-E2 p45-nulled mice show a marked reduction in mGSTA3 (Chan et al, 2001). Also, liver and small intestine from nrf2 Ϫ/Ϫ mice express less mGSTA3 than nrf2 ϩ/ϩ mice Chanas et al, 2002;Thimmulappa et al, 2002).…”
mentioning
confidence: 99%
“…182 However, abnormal response of cells to oxidative stress can cause toxic effects through the production of peroxides and free radicals, leading to damages in RBC skeleton, in normal mechanisms of cellular signaling, in membrane fluidity, and, consequently, it can affect the passage through the microcirculatory network. Thus, impaired RBCs deformability caused by the damages to the structural components of the membrane worsen some pathological situations related to high oxidative stress, such as diabetes, and to microcirculation, such as heart failure and myocardial infarction.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In the case of mice, deficiency transcription factor was observed (p53, JunD, Foxos, and HIF-2alpha), which is responsible for the regulation mechanisms involved in antioxidant secretion (Pouyet and Carrier, 2010). However, Chan et al (2001) showed deficiency of the p45NF-E2 gene, which causes an accumulation of elevated levels of reactive oxygen intermediates in red blood cells. According to Nocchi et al (2014), one of the main symptoms of oxidative stress in mice is impaired bladder activity associated with the deterioration of contractile response.…”
Section: Oxidative Stress In Laboratory Animalsmentioning
confidence: 99%